PENGARUH KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP TINGKAT AUDIT REPORT LAG DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia (BEI) - Az-zukhruf, Ovia Anisa (Pascasarjana Universitas Sultan Ageng Tirtayas, 2023)
The goal of this research was to determine whether and how the reputation of KAP affected the connection between audit committees, institutional ownership, and audit report lateness. In this investigation, we use quantitative methods. This investigation employs both descriptive and causal research methods. Purposive sampling was utilized to choose a total of 105 data points from a pool of 21 mining companies trading on the IDX between 2017 and 2021. Multiple linear regression and moderated regression analysis (MRA) were used to analyze the data in SPSS Version 25. After adjusting for confounding factors, an R-squared value of 0.419 was obtained, indicating that the audit committee variable, institutional ownership, the complexity of the company's operations, and KAP's reputation together explain 41.9% of the variance in the audit report lag variable, while other variables account for the remaining 58.1%. The study found that the reputation of the KAP increases the impact of audit committees on audit report lag, while the reputation of the KAP has no effect on the impact of institutional ownership on audit report lag, and the influence of the complexity of a company's operations is increased by the reputation of the KAP.